27 Monitoring the levels of the reactive oxygen species on the whole heart and in single cardiomyocytes during ischaemia-reperfusion. Issue 24 (24th November 2011) - Andrienko, T N; Rossbach, A M; Carter, S M; Pasdois, P; Halestrap, A P
Abstract : ROS production during ischaemia-reperfusion induces mitochondrial permeability transition pore opening and so mediates reperfusion injury. Several groups have used real-time fluorescence to determine ROS production by isolated cardiomyocytes during simulated ischaemia-reperfusion but protocols and results vary. Few studies have utilised the more pathophysiologically relevant perfused heart. We have developed an ischaemia-reperfusion protocol that exposes isolated rat cardiac myocytes to conditions closely matching ischaemia-reperfusion in the perfused heart. Temperature and [oxygen] are tightly controlled and continuously monitored while ROS production is measured by fluorescence microscopy using dihydroethidium (DHE) or 2′, 7′-dichlorofluorescein (DCF). In parallel real-time multiwavelength surface fluorescence and reflectance were used to monitor autofluorescence and ROS production in the perfused rat heart together with measurements of haemodynamic function and infarct size. In isolated myocytes DCF fluorescence increased continuously throughout the experiment, but with pronounced acceleration at the start of ischaemia and at reperfusion. For DHE, nuclear fluorescence increased steadily during ischaemia but dropped to baseline within seconds of reperfusion. In perfused hearts the pattern of fluorescence change was similar; a rapid increase during onset of ischaemia, a larger increase at ischaemic contracture followed by a rapid decrease on reperfusion. To define the nature of the fluorescence changes, emission spectra were determined on the perfused hearts. These confirmed our conclusion that DHE is not a suitable dye to monitor ROS production in situ. DCF appears suitable for use in cardiomyocytes and we are developing suitable loading protocols for perfused heart measurements.